Sociodemographic factors influencing beliefs and behaviors in herbal medicine use among postpartum mothers in Indonesia - Irna Trisnawati; Mamat Mamat; Ari Antini (Healthcare in Low-resource Settings, 2025)
The incidence of herbal medicine consumption is significant among postpartum mothers. However, its long-term use may pose potential risks. This study aimed to investigate the correlation between sociodemographic factors, beliefs, and behaviors related to the consumption of herbal medicine among postpartum mothers in Indonesia. This study employed a cross-sectional correlational design with a sample of 170 postpartum mothers (1-42 days postpartum), determined using G*Power version 3.1. Purposive sampling was used for participant selection. The variables included sociodemographic factors, beliefs, and behaviors related to herbal medicine consumption. Data were analyzed using the Kruskal-Wallis and Mann-Whitney tests. The findings revealed that residency (p=0.001), age (p=0.043), education level (p=0.0001), number of children (p=0.0001), pregnancy complications (p=0.006), and labor complications (p=0.027) were significantly correlated with beliefs regarding herbal medicine consumption. Meanwhile, age (p=0.039) and number of children (p=0.0001) were significantly correlated with herbal medicine consumption behavior. This study highlights the strong influence of sociodemographic factors on the use of postpartum herbal medicine. While many mothers perceive herbal medicine as beneficial, monitoring its long-term effects and potential risks is essential. Future research should focus on ensuring safe use of herbal medicine, integrating traditional and modern healthcare practices, and enhancing education on evidence-based postpartum care.